'New Zealand passport holder' versus 'New Zealander'? The marginalization of ethnic minorities in the news – A New Zealand case study. (August 2016) - Smith, Philippa K
This article uses critical discourse analysis to investigate audience criticism of the news media's marginalization of ethnic minority members in New Zealand through the use of the words 'New Zealand passport holder'. Following my presentation of a case study where a group of readers objected to these words being used to describe a New Zealander with Kurdish origins, I examine the meaning and use of this descriptor at a time of increased diversity. Analysing a selection of news stories from the beginning of the new millennium, I consider aspects of journalistic practice (namely, news values and the sourcing of information), as well as the wider sociocultural context in which the articles were embedded. I argue that the media, rather than creating prejudice by using 'New Zealand passport holder', reproduced and legitimated the political and public discourse of elite groups that disassociated immigrant groups from mainstream New Zealanders. I conclude by emphasizing the ongoing need for journalist training to include an understanding of how the reproduction of the language and discourse of elite groups in news stories can have a negative effect on the representation of minorities.